2004
DOI: 10.1002/pen.20000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gate freeze‐off time in injection molding

Abstract: Gate solidification time is an important topic in injection molding technology, as it determines cycle time, which itself is an important issue in the balance of the production process. In this work, a study of the effect of both gate and cavity geometries on gate solidification time was conducted, using a commercial polymer, injection molded with constant holding pressure into a rectangular cavity. Three cavity lengths were used, and for each, two cavity thicknesses were adopted. Special dies containing diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…If the fluid centre in the gate is completely frozen, no more melt is moved to the cavity. In this case, the pressure in the cavity changes to atmospheric pressure (Pantani et al 2004). …”
Section: Cavity and Boundary Conditionsmentioning
confidence: 97%
“…If the fluid centre in the gate is completely frozen, no more melt is moved to the cavity. In this case, the pressure in the cavity changes to atmospheric pressure (Pantani et al 2004). …”
Section: Cavity and Boundary Conditionsmentioning
confidence: 97%
“…A general decrease has also been found when increasing the holding time, until to the achievement of a plateau value at about 7 sec. This time at which a plateau in shrinkage is reached is often taken as equal to the gate sealing time 8 and is in fairly good agreement with the value found by analyzing the pressure curves.…”
Section: Resultsmentioning
confidence: 87%
“…18 A characteristic time for cooling can be defined as (6) in which α T is the thermal diffusivity of the polymer and H is the slab half-thickness. At each time, the time which is solidifying can be described by the following equation (7) in which (8) and (9) is a solution valid at short times (t < t c ) whereas (10) is a solution valid at times longer than t c . In eq.…”
Section: Resultsmentioning
confidence: 99%
“…Gate solidification only takes place when the heat lost though the gate walls by conduction overcomes the energy entering the gate from the runner because of convection. As described by Pantani et al [24], the conductive heat lost by transverse conduction in the gate, here denoted as Q cond , is of the order of…”
Section: Morphology Of Micro Featuresmentioning
confidence: 99%
“…However, detailed design of a micro gate is still rare. In conventional injection molding, Pantani et al [24] found that both gate thickness and cavity thickness affected the freeze-off time and they related gate solidification time to cavity pressure-time curves. Their analytical model was used successfully to estimate gate solidification time.…”
Section: Introductionmentioning
confidence: 99%